2020
DOI: 10.1111/bjh.16416
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of R‐BAC in relapsed, refractory mantle cell lymphoma post BTK inhibitor therapy

Abstract: Patients with mantle cell lymphoma progressing on Bruton's tyrosine kinase inhibitor (BTKi) have very poor prognosis and there is currently no standard of care. In this retrospective cohort study, patients progressing on BTKi received R-BAC (rituximab, bendamustine, cytarabine). Overall response rate was 83% (complete response 60%) and 31% were bridged to allogeneic stem cell transplant (alloSCT). Median progression-free survival was 10.1 months (95% confidence interval (CI) 6Á9-13Á3) and median overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 14 publications
(17 reference statements)
4
57
1
1
Order By: Relevance
“…In addition, with this historical HMRN cohort, where 16% received ibrutinib at third line or later, the median OS from the start of third line was only 7 months, indicating that the poor outcomes observed in this setting are not specific to ibrutinib. Promisingly, patients who received post‐ibrutinib R‐BAC in our study showed a strong trend to improved OS, a finding consistent with a recent study illustrating high response rates to R‐BAC post BTK inhibitor (ORR 83%, CR/CRu 60%) 16 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, with this historical HMRN cohort, where 16% received ibrutinib at third line or later, the median OS from the start of third line was only 7 months, indicating that the poor outcomes observed in this setting are not specific to ibrutinib. Promisingly, patients who received post‐ibrutinib R‐BAC in our study showed a strong trend to improved OS, a finding consistent with a recent study illustrating high response rates to R‐BAC post BTK inhibitor (ORR 83%, CR/CRu 60%) 16 …”
Section: Discussionsupporting
confidence: 91%
“…Promisingly, patients who received post-ibrutinib R-BAC in our study showed a strong trend to improved OS, a finding consistent with a recent study illustrating high response rates to R-BAC post BTK inhibitor (ORR 83%, CR/CRu 60%). 16 It was not possible to access data on ibrutinib use at national level but as our series provides a balanced representation of academic centres and DGHs results should reflect all institutions where the drug is prescribed in the UK. Steps taken to mitigate inherent bias of retrospective methodology mean the extent of adverse events were only partially explored and inconsistent timing of response assessments mean data was not suitable for time-dependent analysis and should be interpreted carefully alongside prospective data.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, most patients were unable to receive alternative therapy either because of frailty or disease‐related complications. However, in patients for whom an alternative immunochemotherapy regimen was appropriate some durable responses were seen, supporting other recently published observational data 10,11 . These data also support the now established use of ibrutinib as a bridge to consolidation with allo‐SCT in younger fitter patients, although the numbers are admittedly small.…”
Section: Discussionsupporting
confidence: 84%
“…R-BAC has an ORR of 80% (CR 70%), with a 70% 2-year PFS [55]. In real life experiences, R-BAC has demonstrated to be a promising bridge to transplant scheme, with 22-33% of patients undergoing allo-SCT after achieving a clinical response [27,56]. Given the favorable outcomes observed in terms of ORR and CR, R-BAC can represent an alternative bridging strategy to allo-SCT.…”
Section: Chemo-immunotherapymentioning
confidence: 99%